The effects of work–family conflict, work engagement, and job burnout on self-rated health of public health emergency responders in Jilin Province, China, in the context of the COVID-19 - Hu, Bingqin; Yang, Guofeng; Ma, Jingyu; Chen, Yitong; Cui, Peiyao; Liang, Yifang; He, Xin; Li, Jinghua (Frontiers in Public Health, 2024)
Introduction: Amid sudden public health crises, preserving the well-being and optimal working states of frontline healthcare professionals is imperative for efficaciously managing the emergences.However, there is a paucity of research investigating the health status of frontline healthcare professionals through the perspective of work-family conflict. This study sought to elucidate the complex interrelations between work-family conflict, work engagement, job burnout, and self-rated health among public health emergency responders within the context of the COVID-19 pandemic.Methods: A convenience sampling method was employed to survey 1,309 public health emergency responders at the Jilin Provincial Centre for Disease Control and Prevention. An online survey was administered utilizing a self-constructed questionnaire. The hypothesized relationships between the variables were tested using structural equation modeling.The direct impact of work-family conflict on self-rated health is not significant. The association between work-family conflicts and self-rated health was significantly mediated by work engagement and job burnout respectively. Meanwhile, work engagement and job burnout had a chain mediating effect on work-family conflict and self-rated health.: Work-family conflict plays a critical role in shaping the health and work status of public health emergency responders during public health crises. Organizations and managers should, in their workplace management practices, focus not only on work-related factors but also give due consideration to family-related factors. Supportive policies, including family-friendly initiatives, should be developed to safeguard the health and work engagement of public health emergency responders.